Investigating the Attitude and Self-Confidence Level of Emergency Doctors and Nurses in the Field of Violence Management in the Emergency Department of Urmia University of Medical Sciences - Garkaz, Omid; Atabaki, Peyman; Mohammadi, Neda; Paryab, Sahar; Moradi, Khatire; Mehryar, Hamid Reza (Shahroud Journal of Medical Sciences, 2024)
Introduction: Although the emergency department is known as a potential center of violence and the main reason for the prevalence of violence in these departments is unknown. Due to the lack of registration and reporting systems for these cases, the history of research in this case is limited and there are problems in this field. And this study was conducted with the aim of investigating the attitude and self-confidence level of emergency doctors and nurses in the field of violence management in the emergency department of Urmia University of Medical Sciences.Materials and methods: This descriptive-analytical study was conducted on 187 personnel working in medical education centers of Urmia by census method. The data was collected using the demographic information checklist and Dimond et al.'s questionnaire. After collecting the data, it was entered into SPSS 18 and analyzed with the help of descriptive and analytical statistics.Findings: In this study, the results showed that out of 187 personnel participating in the study, most of the participating personnel were nurses 134(%71.6), age group 138(%73.8) 26 to 35 years old and gender 97(%51.9) were male. And there was a significant relationship between the gender of the emergency department staff and a work experience in the emergency department with all three areas of understanding of violence, self-confidence in managing aggressive behavior and attitude towards safety and responsiveness and security in the workplace in the face of aggression. The age group of the emergency department staff had a significant difference only in the individual's perception of violence, in such a way that younger age groups had lower scores in the perception of violence section.Discussion and conclusion: The issue of violence is a serious issue in the emergency departments of teaching hospitals in Urmia and serious attention should be paid to this point by the relevant authorities. And considering the lower levels of self-confidence of people in the face of aggression among people who have not completed training courses on violence management, the necessity of wider implementation of these courses among the employees of the emergency department in the investigated centers is mandatory.